Brasil, ammistía y memoria - Frajman, Mauricio (2013)
The article analyzes the impunity of the perpetrators of torture and murder during the military dictatorship in Brasil, and how the economical power uses the same methods for repression of their new enemies, the poor mostly black young fellows, and impunity persists.